Epidemiology of chronic lymphocytic leukemia in Chilean and Amerindian population in Chile. Issue 5 (16th April 2022) - Cabrera, María Elena; Marinov, Neda; Roa, Macarena; Castillo, Jorge J.; Matutes, Estella
Abstract: The study aim was to analyze incidence and presentation features of chronic lymphocytic leukemia (CLL) in Chile, in Amerindian population and in non-Native. Between 2012 and 2019, 912 patients were diagnosed, and 13 (1.4%) were Amerindian. The estimated incidence in Chilean population was 1.17/100, 000 person per year, while in Amerindian, 0.09/100, 000 person per year. Median age was 73 years. At diagnosis, 48, 27, and 25%, had low (0), intermediate (I/II) and high-risk (III/IV) disease on Rai classification. Diagnostic immunophenotypic Matutes score was ≥4 in 90%. Median follow-up was 37 months (range 2–87). 5-year OS was 56%, with median overall survival (OS) not reached. It was worse in men, ≥65 years, high-risk and those with increased prolymphocytes (CLL/PL). This study shows low incidence and worse OS in Chilean CLL patients, compared to those from European countries, despite similar clinical features. It also demonstrates that CLL is very uncommon in Amerindian population.